2013
DOI: 10.1073/pnas.1311760110
|View full text |Cite
|
Sign up to set email alerts
|

Lung epithelial branching program antagonizes alveolar differentiation

Abstract: Mammalian organs, including the lung and kidney, often adopt a branched structure to achieve high efficiency and capacity of their physiological functions. Formation of a functional lung requires two developmental processes: branching morphogenesis, which builds a tree-like tubular network, and alveolar differentiation, which generates specialized epithelial cells for gas exchange. Much progress has been made to understand each of the two processes individually; however, it is not clear whether the two process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
231
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(257 citation statements)
references
References 53 publications
24
231
1
Order By: Relevance
“…Yy1 function is thus required in both mesenchymal and epithelial cell layers for the correct development of the respiratory tract. Epithelial inactivation of the Yy1 gene inhibited lung branching but maintained distal epithelial cell differentiation, which agrees with the notion of negative correlation between branching and alveolar differentiation (Chang et al, 2013). The Yy1 mutation also caused the formation of large cysts that mimicked the Shh lung phenotype (Litingtung et al, 1998;Pepicelli et al, 1998).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Yy1 function is thus required in both mesenchymal and epithelial cell layers for the correct development of the respiratory tract. Epithelial inactivation of the Yy1 gene inhibited lung branching but maintained distal epithelial cell differentiation, which agrees with the notion of negative correlation between branching and alveolar differentiation (Chang et al, 2013). The Yy1 mutation also caused the formation of large cysts that mimicked the Shh lung phenotype (Litingtung et al, 1998;Pepicelli et al, 1998).…”
Section: Discussionsupporting
confidence: 85%
“…Recent data indicate that the transition from branching morphogenesis to epithelial cell differentiation depends on control mechanisms involving key players of lung development such as Fgf10 and SOX9. These latter act by regulating the delicate balance between distal and proximal endodermal progenitors, promoting branching and preventing precocious alveolar differentiation (Chang et al, 2013;Volckaert et al, 2013;Yang and Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sox9 regulates Mia1 expression through binding to a SOX consensus sequence in the Mia1 promoter (Xie et al, 1999). Mia1 is also an FGF-regulated protein during lung branching morphogenesis (Lin et al, 2008) and is decreased in expression in the Sox9 mutant lung (Chang et al, 2013). Our data showed that Mia1 mRNA was strongly expressed in primary lacrimal bud tip cells at E13.5 (Fig.…”
Section: Sox9 Regulates the Expression Of Cartilage-associated Factormentioning
confidence: 52%
“…During tracheal morphogenesis, the distribution of the activated ERK1/2 in epithelial cells at terminal lung buds is regulated by Sprouty1/2, which determines mitotic spindle orientation and airway shape (14,15). Furthermore, the Ras-ERK signaling pathway in Sox9 + cells at the branch tips of developing lungs regulates the balance between branching and alveolar differentiation (16). Our findings demonstrate that DA-Raf predominantly inhibits the Ras-ERK signaling pathway in AEC2s during alveolar formation.…”
Section: Discussionmentioning
confidence: 67%
“…The Ras-ERK signaling pathway is one of the key regulators for not only tracheal branching but also alveolar formation in developing lungs (14)(15)(16). The Ras-ERK signaling pathway transmits extracellular stimuli from the plasma membrane to the cytoplasm or the nucleus (17)(18)(19).…”
mentioning
confidence: 99%